Genetic relationship of orchids in the Calanthe group based on sequence-related amplified polymorphism markers and development of sequence-characterized amplified regions markers for some genus/species identification - Nutthapornnitchakul, Surapa; Peyachoknagul, Surin; Sangin, Pattamon; Kongbungkerd, Anupan; Punjansing, Tassanai; Nakkuntod, Maliwan (Agriculture and Natural Resources, 2019)
The Calanthe comprises a group of terrestrial orchid species known for their attractive flowers consisting of three genera (Calanthe, Phaius and Cephalantheropsis) which share many similar characteristics causing difficulty in identification. Here, the genetic relationship of the Calanthe group was studied using sequence-related amplified polymorphism (SRAP) markers. Using 18 primer pairs, 565 fragments were generated in which 562 were polymorphic (99.45%) indicating a high level of polymorphism in the Calanthe. A dendrogram was constructed using the unweighted pair group method with arithmetic mean method. Calanthe orchids were separated into five clades consisting of three groups of the genus Calanthe, one Phaius group and one consisting of Calanthe and Cephalantheropsis species. Overall clusters were in agreement with their morphologies and other reports using DNA sequences of the chloroplast genome, indicating the effectiveness of the SRAP markers; however, C. rubens var. alba was not closely related to C. rubens, suggesting a possible identification error. Sequence characterized amplified regions (SCAR) primers for P. flavus and C. herbacea species identification were also developed. The results showed that PFLF/PFLR primers could be used to amplify the specific fragment of 240 bp only in P. flavus. CHEF/CHER primers were used to amplify the fragment of 430 bp in three species (C. masuca, C. triplicata and C. herbacea) which were in the same clade. SCAR markers were successfully developed for P. flavus identification and detection of the C. masuca-C. triplicata-C. herbacea clade.